RISET PERILAKU KONSUMEN PADA MAHASISWA AKTIF PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS BUNDA MULIA TAHUN AJARAN 2011 – 2012 SEBAGAI PENGUNJUNG LAWSON’S STATION-LODAN - Rustono Farady Marta (Universitas Bunda Mulia, 2014)
Business prospects for a concept of convenience stores are becoming increasingly brighter for business today. One brand of convenience stores emerging in Indonesia is Lawson's Station. The concept of practical and convenient place served to segment the youth market, in accordance with that carried the tagline